Pengaruh Program Flash Sale dan Live Streaming Shopping terhadap Purchase Intention dengan Impulsive Buying sebagai Variabel Mediasi (Studi Kasus pada Pengguna Platform Shopee) - Damayanti, Noviana; Riana, Zenni; Fahmi, Nur Augus (JRMB (Jurnal Riset Manajemen & Bisnis), 2023)
This research aims to determine the influence of flash sales and live streaming on impulsive buying and live streaming on Shopee e-commerce users and to determine the influence of flash sales, live streaming and impulsive buying on purchase intention on Shopee e-commerce users. The research population was undergraduate (S1) students from the Management study program, Faculty of Economics and Business, Islamic University of North Sumatra, class of 2020, totaling 160 people. Sampling in this study used probability sampling with a sampling technique, namely simple random sampling. The data collection technique used was a questionnaire. Data analysis techniques include data quality testing, validity and reliability testing. Based on the analysis results, flash sales have an effect on impulsive buying and purchase intention both simultaneously, partially and also have a significant effect. Live streaming has an effect on impulsive buying and purchase intention both simultaneously, partially and also has a significant effect. Impulsive buying has a significant effect on purchase intention